Hierarchically Engineered Artificial Lamellar Bone with High Strength and Toughness. Issue 3 (29th December 2022) - Zhao, Yonggang; Zheng, Jingchuan; Xiong, Yang; Wang, Hetong; Yang, Shuhui; Sun, Xiaodan; Zhao, Lingyun; Mikos, Antonios G.; Wang, Xiumei
Abstract : Complex hierarchical architectures are ubiquitous in natural hard tissues, which comprise an elaborate assembly of hard and soft phases spanning from the nanoscale to the macroscale. The elegant architectures grant unique performance in terms of strength and toughness, but the biomimetic fabrication of synthetic materials with highly consistent structural and mechanical characteristics with natural counterparts remains a great challenge. Here, a centimeter‐size artificial lamellar bone is successfully fabricated for the first time via a well‐orchestrated "multiscale cascade regulation" strategy combining multiple techniques of molecular self‐assembly, electrospinning, and pressure‐driven fusion from molecular to macroscopic levels. The bulk artificial lamellar bone that is composed of hierarchically assembled mineralized collagen fibrils with a waiver of any synthetic polymer highly resembles the chemical composition, multiscale structural organization, and rotated plywood‐like structure of natural lamellae, thus achieving a good combination of lightweight and high‐stiffness ( E y ≈ 15.2 GPa), ‐strength ( σ f ≈ 118.4 MPa), and ‐toughness ( K JC ≈ 9.3 MPa m 1/2 ). This multiscale cascade regulation strategy can break through the limitations of a single technique and enable the construction of elaborate composite materials with multiscale step‐by‐step regulations of hierarchically structural organizations for unique mechanical properties. Abstract : A well‐orchestrated facile "multiscale cascade regulation" strategy is developed for mimicking the plywood‐like structure of natural lamellar bone.